Upaya Meningkatkan Motorik Halus Anak Melalui Kegiatan Menggunting dan Menempel Pada Kelompok B Di Tk Aisyiyah Bustanul Athfal II Tumampua, Kab. Pangkep, Kec. Pangkaje’ne - Sartika, Sartika; rahayu, sri reski (Jurnal Guru Pencerah Semesta, 2023)
AbstracThe capability of pupils in the grade/class B3 TK Aisyiyah Bustanul Athfal II Tumampua in case of fine motor especially for cutting and sticking does not match slightly teacher’s desired expectation yet by reason of scared or fearful feelings in using cutter and in handling glue as well. Whereas, in human growth a physical development of motor has the same important role as cognitive development , social behavior, and personality. Cutting and sticking activities are aimed to enhance children’s fine motor capability. Method used in enhancing the said capability is demonstration and assignment. As an advantage in promoting the finemotor capability is to practice a coordination of hands, eyes, and concentration; to increase self confidence; to write smoothly; to convey expression; and to improve cognitive development. This study utilizes action research in class assigning teacher as researcher. Two-round spiral system of early reflection is engaged in this research. Each round comprises action plan arrangement, action performance, observation and reflection. The research object is the grade/class B3 TK Aisyiyah Bustanul Athfal II Tumampua. Based on the analysis, it is discovered that through cutting and sticking the pupils are able to enhance their fine motors, that is. A conclusion of the research is that the cutting and sticking are able to enhance the fine motor capability of the grade/class B3 TK Aiyiyah Bustanul Athfal II Tumampua.